Health‐Related Quality of Life in Children, Adolescents, and Adults With a Fontan Circulation: A Meta‐Analysis. Issue 6 (17th March 2020) - Marshall, Kate H.; D'Udekem, Yves; Sholler, Gary F.; Opotowsky, Alexander R.; Costa, Daniel S. J.; Sharpe, Louise; Celermajer, David S.; Winlaw, David S.; Newburger, Jane W.; Kasparian, Nadine A.
Abstract : Background: People with a Fontan circulation experience a range of physical, psychosocial and neurodevelopmental challenges alongside, or caused by, their cardiac condition, with significant consequences for health‐related quality of life (HRQOL). We meta‐analyzed HRQOL outcomes reported by people with a Fontan circulation or their proxies and evaluated predictors of poorer HRQOL. Methods and Results: Six electronic databases were searched for peer‐reviewed, English‐language articles published before March 2019. Standardized mean differences (SMD) were calculated using fixed and random‐effects models. Fifty articles reporting on 29 unique studies capturing HRQOL outcomes for 2793 people with a Fontan circulation and 1437 parent‐proxies were analyzed. HRQOL was lower in individuals with a Fontan circulation compared with healthy referents or normative samples (SMD, −0.92; 95% CI, −1.36 to −0.48; P <0.001). Lower scores were reported across all HRQOL domains, with the largest differences found for physical (SMD, −0.90; 95% CI, −1.13 to −0.67; P <0.001) and school/work functioning (SMD, −0.71; 95% CI, −0.90 to −0.52; P <0.001). Meta‐regression analyses found no significant predictors of self‐reported physical functioning, but older age at Fontan operation was associated with poorer emotional functioning (β=−0.124; P =0.004), and diagnosis of hypoplastic left heart was associated with poorer social functioning (β=−0.007; P =0.048). Sensitivity analyses showed use of the PedsQL Core Module was associated with lower HRQOL scores compared with the Short‐Form Health Survey‐36. Conclusions: HRQOL outcomes for people with a Fontan circulation are lower than the general population. Optimal care acknowledges the lifelong impact of the Fontan circulation on HRQOL and offers targeted strategies to improve outcomes for this growing population.